Financial Liberalization and Real Investment : Evidence From Turkish Firms - Sancak, Cemile (IMF Working Papers; Working Paper ;, 2002)
There is increasing emphasis on the importance of efficient financial markets for sustained real investment and economic growth, yet limited empirical research on the effects of the deregulation of financial markets on the firm's investment decisions. The purpose of this paper is to model the impact of financial reforms on borrowing constraints faced by firms and to test the impact of financial reforms on the investment decisions of firms in Turkey. To do so, the paper builds a dynamic investment model, where financial variables and real investment are linked through the net present value of the firm. The derived investment model is employed to test whether Turkey's efforts at financial liberalization in 1980 were able to relax the borrowing constraints faced by Turkish firms. A dynamic panel data methodology is used on a panel data set of 1036 Turkish firms over the 1983-86 period. In addition, time-series analysis is employed on Turkish aggregate data over the 1971-91 period.